Life. after. Theory : Jacques Derrida, Toril Moi, Frank Kermode and Christopher Norris. - Payne, Michael (Bloomsbury Publishing PLC, 2003)
Is there life after theory? If the death of the Author has now been followed by the death of the Theorist, what's left? Indeed, who's left? To explore such riddles Life. After.Theory brings together new interviews with four theorists who are left, each a major figure in their own right: Jacques Derrida, Frank Kermode, Toril Moi, and Christopher Norris. Framed and introduced by Michael Payne and John Schad, the interviews pursue a whole range of topics, both familiar and unfamiliar. Among other things, Derrida, Kermode, Moi and Norris discuss being an outsider, taking responsibility, valuing books, getting angry, doing science, listening to music, remembering Empson, rereading de Beauvoir, being Jewish, asking forgiveness, smoking in libraries, befriending the dead, committing bigamy, forgetting to forget, thinking, not thinking, believing, and being mad. These four key thinkers explore why there is life after theory...but not as we know it. Jacques Derrida is Professor at the +cole des Hautes +tudes en Sciences Sociales in Paris. He is the author of a range of extraordinarily influential works including Of Grammatology, Writing and Difference and Dissemination. Sir Frank Kermode is a former King Edward VII Professor of English Literature at the University of Cambridge and author of, among many other books, The Sense of An Ending: Studies in the Theory of Fiction, Shakespeare's Language, and Not Entitled, his memoirs. Toril Moi is James B. Duke Professor of Literature and Romance Studies at Duke University. Her books include Sexual/Textual Politics: Feminist Literary Theory, Simone de Beauvoir: The Making of an Intellectual Woman and What Is a Woman? And Other Essays. Christopher Norris is Distinguished Research Professor in Philosophy at the University of Cardiff. He has published some twenty books to date, including, most recently,